O crescimento de Aegla leptodactyla Buckup & Rossi (Crustacea, Anomura, Aeglidae) - Noro,Clarissa Köhler (2003)
The growth study, in length and weight, of Aegla leptodactyla Buckup & Rossi, 1977, was developed based on biometric data of 2,435 specimens collected from Rio da Divisa, a tributary of the Rio Silveira, district of São José dos Ausentes, Rio Grande do Sul State, Brazil. The samplings were realized from April/2000 to July/2001. The captured specimens had recorded the Sex and the length and width of cephalothorax. The specimens from June/2000, November and May/2001 were weighted, and those from June and July/2001 had recorded their length and width of the chelipeds. For the description of the growth the von Bertalanffy's model was utilized. The growth curves in length (mm), for data obtained through the modal progression, are described by the equations: Ct = 19.83 [1- e - 0,0023 (t +55,5)] for males and Ct = 18.096 [1- e - 0,0024 (t +48,6)] for females. For data obtained through the progression of age group means, the equations for males and females are, respectively, Ct = 18.15 [1- e - 0,0027 (t +52)] and Ct = 20.7 [1- e - 0,002 (t +63,4)]. For the growth description in weight (g), for data obtained through modal progression, the equations are: Pt = 3.88 [1- e - 0,0023 (t +55,5)]3,073 for males and Pt = 2.78 [1- e - 0,0024 (t +48,6)]3,1046 for females, and for data obtained from progression of age group means: Pt = 2.96 [1- e - 0,0027 (t +52)]3,073 (males) e Pt = 3.65 [1- e - 0,002 (t +63,4)]3,1046 (females). The analysis of covariance did not record significant differences between the length of right and left chelae, of males and females.